Use of Fungal Humus for 1,1,1-Trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) Polluted Soil Treatment - Van Chung, Tran; Ngoc Khue, Do; Binh Minh, Do; Cheng, Francis (Asian Journal of Chemistry, 2010)
This paper, describes the use of fungal humus, the residual compost waste generated by mushroom production, for treatment of DDT polluted soils instead of the use of fungi. The capacity of using the fungal humus from culture of Japanese and Vietnamese fungi such as Pleurotus sajo caju, Pleurotus ostreatus, Hipsizygus marmorenus, Lentinus edodes to treat DDT polluted soils has been studied. This work focused only in the efficiency of DDT biodegradation by the fungal humus. The obtained data showed that the ratio of the fungal humus and soils mixture being from 1/10 to 1/5 for 30 days, may degrade DDT in the soils with the high efficiency of 50-70 %. The activity of ligninolytic enzymes in the experiment such as lignin peroxidase (LiP) and mangan peroxidase (MnP) has had an influence on the efficiency of DDT degradation in the soil.